Volume 4A: Dynamics, Vibration, and Control 2016
DOI: 10.1115/imece2016-67673
|View full text |Cite
|
Sign up to set email alerts
|

A Bionic Test-Bed for Sensing and Balance Augmentation in Biological Applications

Abstract: In this research, we are working to develop a wearable device for stabilizing walking in dachshunds with spinal cord injuries. Our approach is to use sensors on the dog to measure the angle of the torso and stimulate leg motion to balance the animal during standing and walking. The first step in this work is to develop a mechanical test-bed in order to replicate the motion and muscle response during the gait of the dog. This testbed will be used for exploring sensor device operation and for developing appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The trajectory of the normal walking gait for typical dog have been previously studied [ 39 ] in order to identify the hip, knee and hock angles during walking. VICON [ 44 ] video tracking software was used to record the motion of markers attached to the hock, knee, and hip joint of an adult dog while walking normally on a treadmill at a speed of 5 km/h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trajectory of the normal walking gait for typical dog have been previously studied [ 39 ] in order to identify the hip, knee and hock angles during walking. VICON [ 44 ] video tracking software was used to record the motion of markers attached to the hock, knee, and hip joint of an adult dog while walking normally on a treadmill at a speed of 5 km/h.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work [ 39 ], an earlier version of the test-bed was developed with a single motorized axis, based of veterinarian experience that the hock joint was used by dogs as the primary balancing joint. This work demonstrated the efficacy of using the bionic test bed for development, but also pointed to the need for a more complete hindquarters model of the dog.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [17], we designed and built a FES-based wearable device using an Arduino Uno board that could be used for stimulation of hindleg muscles of dogs suffering from spinal cord injury. The sensing core of this balancing device includes a single IMU attached to the pelvis of the dog to gain data about pelvis angle of rotation.…”
Section: A Background On Functional Electrical Stimulation Devices Anmentioning
confidence: 99%
“…In our previous study [17], we showed VICON software could be used to obtain various data about animal gait including changes in animal joint angles during each step. We used Fourier series to approximate VICON discrete time data about joint angles as continuous time functions.…”
Section: Hardware Set-upmentioning
confidence: 99%
See 1 more Smart Citation